MplusAutomation: An R Package for Facilitating Large-Scale Latent Variable Analyses in Mplus. Issue 4 (4th July 2018) - Hallquist, Michael N.; Wiley, Joshua F.
Abstract : MplusAutomation is a package for R that facilitates complex latent variable analyses in M plus involving comparisons among many models and parameters. More specifically, MplusAutomation provides tools to accomplish 3 objectives: to create and manage M plus syntax for groups of related models; to automate the estimation of many models; and to extract, aggregate, and compare fit statistics, parameter estimates, and ancillary model outputs. We provide an introduction to the package using applied examples including a large-scale simulation study. By reducing the effort required for large-scale studies, a broad goal of MplusAutomation is to support methodological developments in structural equation modeling using M plus .